A new method for drying waterlogged wooden artefacts: comparison of cyclical pressure drops with conventional methods. - SANYA, Emile A; REZZOUG, Sid-Ahmed; ALLAF, ADÉCHINA. ERIC (My University, 2003)
A new drying process by cyclical pressure drops (Déshydratation par Détentes Successives: DDS) was devised and developed for drying waterlogged and fresh woods. This study examines the effectiveness of this drying process compared with the standard drying processes such as hot-air, continuous vacuum and freeze-drying. For archaeological specimens, parameters such as dimensional stability (directional Sd or volumetric shrinkage Sv) and colour stability are important, as well as subjective parameters such as cracks, splits and distorsions. The DDS process gives satisfactorily results coupled with a high drying rate. Small values of shrinkage were obtained with DDS: Sv values were in the range of 7-13% compared with 11-17% for vacuum drying, 18-36% with hot-air, and 8-11% for freeze-drying. It is concluded that DDS is a suitable and fast way of drying waterlogged and fresh woods.
Keywords: Conservation; waterlogged wood; dehydration; colour preservation; dimensional stabilization; shrinkage.